Desenvolvimento de reator eletroquímico de leito particulado para processo hidrometalúrgico de produção de cobre - Costa, Pedro Henrique de Britto (Universidade Federal de São Carlos, 2014)
Typical hydrometallurgical processes for metal production such as zinc, copper, nickel and cobalt, among others, are carried out in huge electrochemical tankhouses since only low current densities can be applied in order to obtain a good deposit quality. In this work, the development of a new equipment was proposed for metal electrowinning from the leached ore extract aiming to overcome the limitations reported. The two pieces of equipment proposed are called three-dimensional electrochemical reactors with pulsed-bed electrode (PBE) and spouted-bed electrode (SBE), which are composed of small particles that provide a great improvement in specific surface area, using only a small amount of reactor volume, allowing high current densities to be applied, consequently diminishing the need for huge electrowinning tankhouses. An analysis and comparison of these two electrodes were based on the dependent variables current efficiency (CE), energy consumption (EC) and space-time yield (Y), that are considered the most important variables affecting electrochemical processes and reactors. Designs of experiments (DoE) were carried out in order to determine the best conditions achievable and also to obtain a deep understanding of the influences of each variable on the electrowinning process. In order to do that, the current density (i), time of packed bed (tp), time of fluidized bed (tf), sulfuric acid concentration (Cs) and electrode thickness (e) were studied. It was verified that time of fluidized bed has a negative effect on the process and must be reduced to its minimal value, which is 2 s, that is enough to recirculate and mix the particles in order to prevent from electrode clogging and also short-circuit. During the packed bed, best electrodeposition rates are achieved and it must be increased to its maximum possible value. Current density also must be increased in order to prevent from anodic zones during the fluidization step. Once established that low CE values are due to existence of anodic zones, it was clear the need of reducing acid concentration to its minimum value (100 g L-1), since lower values would increase the cell potential (Ecell) and cause a dendritic growth that is the major cause of short-circuit. Finally, the best condition was obtained by the union of all this information, allied with the reduction of electrode thickness, in order to make the overpotential profile more even inside the electrode. Thus, the best condition for copper electrowinning using a PBE was 2600 A m-2 of i, 54 s of tp, 116 g L-1 of H2SO4 and 2.4 cm of electrode thickness, providing 100% of EC, 1.7 kWh kg-1of CE and 76 kg m-3h-1of Y. These values are considered much superiors to those found in the conventional copper electrowinning processes. From this experience, it was decided to study the copper electrowinning using a SBE which also have promising features in this field. In this way, the independent variables current density (i), supporting electrolyte concentration (Cs), pH, electrolyte temperature (T) and electrode thickness (e) were studied. It was verified that, in accordance with the results of PBE, the current density must be increased in order to prevent from anodic zones; more concentrated supporting electrolytes improve CE and also decrease Ecell; low pH values also decrease Ecell, although values lower than 1.0 depreciate CE; and the electrolyte temperature have more impact in the dissolution rate than in the electrodeposition rate. In this case, the electrode thickness doesn t improve much, thus the best condition obtained for copper electrowinning into the SBE was: 1.8 M Na2SO4; pH 1.0; T = 40 ºC and e = 2.1 cm, could achieve 97% EC, 2.7 kWh kg-1 CE and 109 kg m-3h-1 Y. With exception to the energy consumption, the SBE presented a better performance than the conventional reactors used in industry, even better than the PBE, once it worked at 100% CE in many conditions imposed. It also presented very much higher Y values than the PBE. Even though, taking into account the hydrometallurgical industry needs, the PBE presented results that would attend those needs, once cost is the major issue in most of industry. Moreover, a difference of only 100 mV in cell potential is responsible for a big reduction in energy consumption and, consequently, cost of production.
Keywords: Engenharia eletroquímica; Reator eletroquímico; Eletrodo de leito pulsante; Eletrodo de leito de jorro; Eletrorrecuperação de cobre; Hidrometalurgia; ENGENHARIAS::ENGENHARIA QUIMICA